1988
DOI: 10.1007/bf00273669
|View full text |Cite
|
Sign up to set email alerts
|

Classifying seedlots of Picea sitchensis and P. glauca in zones of introgression using restriction analysis of chloroplast DNA

Abstract: Chloroplast DNA (cpDNA) restriction analysis was used to classify five reforestation seedlots as to species. The material included two Sitka spruce (Picea sitchensis (Bong.) Carr.), one white spruce (P. glauca (Moench) Voss) from interior British Columbia, and two putative hybrid seedlots from the coast-interior introgression zone in British Columbia. The cpDNA patterns generated by Bam-HI and Bc1-I from individual trees of Sitka spruce, white spruce, western white spruce (P. glauca var. albertiana (S. Brown))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…However, the problem of these biochemical marker assays is that they are affected by plant phenological stage and their limited availability, and therefore, they would never allow for a genome-wide scan of variability (as only 0.1% of the total variation is detectable by this technique, [19]). An invaluable alternative offered DNA-based markers, such as restriction fragment length polymorphism (RFLPs) [20][21][22]. Finally, the possibility to rapidly amplify specific DNA fragments in vitro via polymerase chain reaction (PCR) [23] revolutionized the generation of molecular markers, leading to diverse sets of diagnostic DNA-marker systems with or without a priori sequence knowledge, such as random amplified polymorphic DNA (a.k.a RAPD) [24], amplified fragment length polymorphism (a.k.a AFLP) [25], simple sequence repeats (a.k.a SSRs or microsatellites) [26], single nucleotide polymorphisms (a.k.a SNPs) [27,28] and variations thereof [29,30].…”
Section: Marker Types and Their Applicationsmentioning
confidence: 99%
“…However, the problem of these biochemical marker assays is that they are affected by plant phenological stage and their limited availability, and therefore, they would never allow for a genome-wide scan of variability (as only 0.1% of the total variation is detectable by this technique, [19]). An invaluable alternative offered DNA-based markers, such as restriction fragment length polymorphism (RFLPs) [20][21][22]. Finally, the possibility to rapidly amplify specific DNA fragments in vitro via polymerase chain reaction (PCR) [23] revolutionized the generation of molecular markers, leading to diverse sets of diagnostic DNA-marker systems with or without a priori sequence knowledge, such as random amplified polymorphic DNA (a.k.a RAPD) [24], amplified fragment length polymorphism (a.k.a AFLP) [25], simple sequence repeats (a.k.a SSRs or microsatellites) [26], single nucleotide polymorphisms (a.k.a SNPs) [27,28] and variations thereof [29,30].…”
Section: Marker Types and Their Applicationsmentioning
confidence: 99%
“…Both views are mainly based on morphological and crossability analyses. Recently, isozyme and chioroplast DNA (cpDNA) analyses have been used to reconstruct the phylogenetic relationships among conifer forest tree species (Sigurgeirsson & Szmidt, 1988;Wang & Szmidt, 1990;Shurkhal et at., 1992;Wagner et at., 1992). Most cpDNA analyses conducted to date have examined restriction fragment length polymorphisms (RFLPs) over the entire chloroplast genome or nucleotide sequences of a single gene.…”
Section: Introductionmentioning
confidence: 99%
“…Natural hybridization and introgression in sympatric area for examples between P. mariana and P. rubens (Perron and Bousquet 1997) and P. sitchensis and P. glauca (Szmidt et al 1988), and other combination (Sutton et al 1991;Rajora and Dancik 2000), were reported. The introgression increases variability of populations or species.…”
Section: Comparative Analysis Of Cma-banded Karyotype Among Picea Taxamentioning
confidence: 96%